When Newsroom Tears Go Viral: A Sentiment Analysis of Public Response to Media Layoffs in Indonesia - Assyari Abdullah; Dwi Sutri Astuti; Edison Edison; Mustafa Mustafa; Muhammad Soim; Yefni Yefni; Yasril Yazid; Jayus Jayus; Sumaiyah Sumaiyah; Sofiyanita Sofiyanita; Akmal Khairi (Jogjakarta Communication Conference (JCC), 2026)
The recent phenomenon of layoffs (PHK) in the Indonesian media industry has triggered an emotional public response, especially when the event involves figures who have built close relationships with audiences. This study aims to analyze public sentiment towards the viral farewell moment of KompasTV presenter Gita Maharkesri, as a symbol of the humanitarian crisis in the media workplace. Data was collected from 2,238 user comments on the Antaranews YouTube video using a crawling technique using the YouTube Data API v3 and analyzed using a Python-based Big Data Analytics approach in Google Colab. The results show that the majority of comments are neutral (73.1%), followed by positive comments (14.1%) and negative comments (12.8%). Positive comments reflect a strong parasocial relationship, characterized by words such as